PAVEMENT INTERNET AND DIGITAL INVISIBILITY IN THE MARIKANA MASSACRE - Walton, Marian Nicole (AoIR Selected Papers of Internet Research, 2014)
In many parts of Africa, the term ‘pavement radio’ (from the French radio trottoir) has been used to describe forms of colloquial political talk in African towns and cities, wherever popular unofficial discussion of current affairs takes place, extending into popular media (Ellis, 1989; Nyamnjoh, 2005. Wasserman, 2010). These informal political conversations are extended by mobile phones. Beyond the well- documented sites of ‘Arab Spring’ revolts, mobile communication helped the emergence of local citizen journalism in Southern Africa. (Mare, 2013). In South Africa, Facebook is used by a growing and influential group and is making a mark on local politics (Hyde- Clarke & Walton, 2013).